Pandemic and Online Learning at Engineering Colleges - Ayuningrum, Erica Devi; Wihidayat, Endar Suprih; Liantoni, Febri (IJIE (Indonesian Journal of Informatics Education), 2023)
The Covid-19 pandemic has resulted in social restrictions being implemented in all sectors of life, including the scope of education. The closure of schools, higher education, and other educational institutions resulted in face-to-face learning needing to be carried out as usual. Therefore, online learning is a learning strategy that can be applied in times of crisis like this. Application of online learning, which is carried out without planning and suddenly makes several obstacles arise when this learning is carried out. The purpose of this study is to find out what problems arise when implementing online learning in engineering universities during a pandemic and what solutions can be applied to overcome them. This research is a systematic literature review research with keywords used, namely "online learning" or "online course" and "covid-19" or "pandemic" or "Covid 19". In searching articles, articles that are indexed in the Scopus database are used and are limited to publication years, namely from 2019-2022 (during the COVID-19 pandemic). This study used descriptive analysis with secondary data sources. From the results of this study, the application of online learning, for now, is considered the best solution so that learning can still be carried out. But besides that, there are still many obstacles found in its application due to the need for careful planning and preparation for its implementation. Other obstacles are both technically, facilities, and infrastructure, as well as from the human resources themselves. It is hoped that in the future, the solutions found can add insight and be used as a reference in the application of online learning to be effective and better.